2021
DOI: 10.1155/2021/6636510
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of ROS‐ and BECN1‐Mediated Autophagy by Human Telomerase Reverse Transcriptase in Glioblastoma

Abstract: Glioblastoma (GBM) is the most common and aggressive malignant brain tumor with high morbidity and mortality. Human telomerase reverse transcriptase (hTERT), the catalytic subunit of human telomerase, is overexpressed in most cancers including GBM. It is well known that hTERT can compensate telomere shortening to immortalize cells. However, in addition to the canonical function, hTERT has the roles beyond canonical telomere maintenance. To further understand the effects of hTERT on glioblastoma progression, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Because autophagy is a key molecular mechanism for immune function and telomerase has been shown activate autophagy in different cells types 72-75 , we hypothesised that gut macrophage autophagy would be affected in the absence of telomerase. Our data show that there is a significant decrease in autophagosomes, as assessed by LC3B puncta, in the mpeg + gut cell population with old age, which again is accelerated in the absence of telomerase ( Fig 4D), D1) ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because autophagy is a key molecular mechanism for immune function and telomerase has been shown activate autophagy in different cells types 72-75 , we hypothesised that gut macrophage autophagy would be affected in the absence of telomerase. Our data show that there is a significant decrease in autophagosomes, as assessed by LC3B puncta, in the mpeg + gut cell population with old age, which again is accelerated in the absence of telomerase ( Fig 4D), D1) ).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they may be better explained by non-canonical functions of telomerase. Telomerase is not only capable of restoring telomeres (canonical function) but also of performing non-canonical functions involved in the regulation of cell survival, inflammation and autophagy [72][73][74][75] (recently reviewed here 21 ). Here, we identified a telomerase-dependent decrease in autophagosomes (LC3B puncta) in gut mpeg + cells with ageing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telomerase also participates in the regulation of autophagy. It is reported that downregulation of telomerase activity impaired autophagy function, leading to the overproduction of ROS [66]. Moreover, Green et al also demonstrated that telomerase participated in the cellular response to oxidative stress by regulating autophagy, giving a further verification about interaction between telomerase and autophagy [67].…”
Section: Irisin Elevates the Function Of Telomerasementioning
confidence: 95%
“…The interplay between telomerase and autophagy was shown in several studies on cancer. Ding et al showed that downregulation of hTERT reduced autophagy and decreased BECN1 (Beclin 1, coiled-coil, moesin-like BCL2-interacting protein) in glioblastoma cells [106]. These cells displayed enhanced levels of ROS and ultimately died.…”
Section: Autophagymentioning
confidence: 99%